ANALYSIS OF LEARN DISCIPLINE IN IMPLANTATION CHARACTER EDUCATION OF IVA STUDENTS AT SD NEGERI 5 PANJER IN 2018 - Rokhmaniyah Rokhmaniyah; Risma Mila Ardila (Universitas Sebelas Maret, 2018)
This article describes the results of the study which aims to: (1) analyze the learning discipline of IVa students of SD Negeri 5 Panjer in 2018; (2) describes the teacher's efforts in overcoming students' indiscipline of learning. This research approach is qualitative by descriptive method. Data collection techniques used are observation, interviews, and documentation. The subjects of this study were students of grade IVa SD N 5 Panjer. Data sources of this study are students, teachers, and principals. To maintain the validity of the research data techniques and source triangulation were used. The results showed that the indiscipline of IVa class students included arriving late, not paying attention to the teacher's explanation, entering-leaving the classroom without permission, not collecting tasks on time, not carrying school tools, and skipping school. The efforts made by the teacher overcoming the above include understanding the characteristics of students and give a warning and advice.